Mechanism of penicillin action: penicillin and substrate bind covalently to the same active site serine in two bacterial D-alanine carboxypeptidases. - Yocum, R R (1979)
It has been hypothesized that penicillin acts as a structural analog of the acyl-D-alanyl-D-alanine terminus of nascent bacterial cell wall and that it consequently binds to and acylates the active site of the enzyme(s) that crosslinks the cell wall to form an inactive penicilloyl enzyme [Tipper, D.J. & Strominger, J.L. (1965) Proc. Natl. Acad. Sci. USA 64, 1133-1138]. This study directly proves that penicillin acylates the active site of two penicillin-sensitive enzymes, D-alanine carboxypeptidases from Bacillus stearothermophilus and Bacillus subtilis. Active site peptides were generated by chemical or enzymatic cleavage of these carboxypeptidases after covalently labeling with [14C]penicillin G or after trapping an acyl-enzyme intermediate derived from the depsipeptide substrate. [14C]diacetyl-L-lysyl-D-alanyl-D-lactate. The amino acid sequences of the penicillin- and substrate-labeled peptides were identical. Both penicillin and substrate were covalently bound via an ester linkage to the same active site residue, a serine at position 36 of the B. stearothermophilus carboxypeptidase and the corresponding serine in the B. subtilis carboxypeptidase. The two D-alanine carboxypeptidases showed significant homology around the active site. Moreover, homology between these two enzymes and four beta-lactamases of known sequence suggests that these two groups of enzymes are evolutionally related.